Digging up Jericho (Oxford, UK)
ix, 328 sayfa
Keywords: “Digging Up Jericho: Past Present and Future, arising from a conference exploring the heritage, archaeology and history of the Jericho Oasis, includes contributions by 21 internationally significant scholars. It will appeal to scholars and students in Near Eastern prehistory, Islamic archaeology, public archaeology, the history of archaeology, and cultural heritage management. Jericho has had a profile beyond academia, and the volume will also appeal to anyone interested in the archaeology and heritage of Jericho, biblical archaeology and, more broadly, Israel and Palestine. This is the first volume to offer a holistic perspective on the research and public value of the site of Jericho – an iconic site with a long and impressive history stretching from the Epipalaeolithic to the present day. Once dubbed the ‘Oldest City in the World’, it has been the focus of intense archaeological activity and media interest in the 150 years since its discovery. From early investigations in the 19th century, through Kathleen Kenyon’s work at the site in the 1950s, to the recent Italian-Palestinian Expedition and Khirbat al-Mafjar Archaeological Project, Jericho and its surrounding landscape has always played a key role in our understanding of this fascinating region. Current efforts to get the site placed on the World Heritage List only enhance its appeal. Covering all aspects of work at the site, from past to present and beyond, this volume offers a unique opportunity to re-evaluate and assess the legacy of this important site. In doing so, it helps to increase our understanding of the wider archaeology and history of the Southern Levant“ --